Educação profissional : o potencial formativo do trabalho de conclusão de curso dos cursos técnicos do centro Paula Souza. - Gamba, Maristela de Carvalho (2016)
This research has had its concern from my professional experience as a technical school professor and as a Final Paper advisor for Computing, Internet Computing and Digital Games Coding courses in a technical school in Santos that has the Final Paper as its graduating proposal as seen in the Political Pedagogical Project. The research meant to discover if the institution¿s graduates perceived the Final Paper as an activity that contributed to their professional development. In order to do so, the research¿s main question was elaborated: How do graduates perceive the contributions the Final Paper had in their professional practice? The theoretical grounding of this project is based on the works of Demo, Schön, Freire, and others who pointed out the importance of the graduating subject to build its own knowledge, valuing the experience as a learning source and developing its ability to think critically and assign meaning to what is being taught. The research, with a quantitative approach, was achieved by the focus group method with graduates from Computing and Internet Computing classes from a technical school from Santos. The focus group was meant to investigate group members¿ perceptions of the researched theme and the building of the scientific paper. The results obtained from the focus group show that the graduates perceive the Final Paper as an important practice for the development of their autonomy since they have had the opportunity to experience research techniques which are fundamental for project development. Besides, they pointed out the group project as one of their main difficulties claiming that not everyone has the same commitment to the project and its deadlines. They claimed that, to overcome this difficulty, they had to learn how to first of all organize the group and mainly how to properly communicate. To these graduates the Final Paper development was a rough path, even though it brought satisfaction seen that they had to overcome several difficulties on the way. However, they also said that seeing the final project was a reason to be proud. The results of the research showed that even though the Final Paper is a practice with difficulties in the beginning since the biggest part of the work come from individual efforts, after the first rough steps most of the graduates get involved with the project and start to understand the value of searching for knowledge and turning it into concrete actions that can solve problems they might face along the way.